2008
DOI: 10.1007/s12031-007-9026-6
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Alzheimer’s Disease and the NOS3 gene Glu298Asp Polymorphism in Chinese

Abstract: The oxidative stress caused by nitric oxide (NO) in the brain has been proposed as a pathogenic mechanism in Alzheimer's disease. Endothelial NO synthase (ecNOS) produces the majority of circulating NO. The biological functional and genetic association studies suggested that the Glu298Asp polymorphism of the ecNOS gene (NOS3) may be a genetic risk factor for late-onset Alzheimer's disease (LOAD). To investigate an association between the NOS31 Glu298Asp polymorphism and sporadic LOAD in Chinese, we examined 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…1 ). 23 case-control studies from 21 publications 2 6 7 8 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 including 5,670 cases and 5,046 controls were used to evaluate the association of G894T polymorphism with AD risk ( Table 1 ). Sample sizes ranged from 102 to 1,369 (median 365).…”
Section: Resultsmentioning
confidence: 99%
“…1 ). 23 case-control studies from 21 publications 2 6 7 8 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 including 5,670 cases and 5,046 controls were used to evaluate the association of G894T polymorphism with AD risk ( Table 1 ). Sample sizes ranged from 102 to 1,369 (median 365).…”
Section: Resultsmentioning
confidence: 99%
“…Association between AD and the NOS3 gene polymorphism 247 in Asians. Eight studies [7,12,14,15,19,[23][24][25] were included in the subgroup of LOAD and four studies [7,12,15,25] were included in the subgroup of EOAD.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Sensitivity analysis showed that the study of Dahiyat et al [12], Styczynska et al [21], and Wang et al [23] was the origin of the heterogeneity. When we excluded the report by Dahiyat et al, Styczynska et al, and Wang et al, the heterogeneity disappeared and still no significant association was observed between NOS3 Glu298Asp polymorphism and AD risk.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The homozygous Glu 298 genotype has been found significantly over-represented in late-onset sporadic AD patients compared with controls [145]. Very recently, Wang and coworkers [146] replicated this finding in a large Chinese cohort. This suggests that NOS3 Glu 298 homozygous genotype might be a risk factor for sporadic AD.…”
Section: Endothelial Nitric Oxide Synthasementioning
confidence: 82%